An elastic model for the prediction of the lateral response of Cross-Laminated Timber shear walls with openings. (1st January 2023) - D'Arenzo, Giuseppe
Highlights: An analytical model describing the elastic lateral response of monolithic shear walls with openings is presented. Expressions to calculate the rocking stiffness, the lateral displacements, and the tensile forces in the hold down connections are provided. A parametric analysis highlighting the structural components that most influence the lateral response of CLT shear walls with openings is conducted. Abstract: This paper presents an analytical model for the prediction of the lateral response of Cross-Laminated Timber shear walls with openings. The model specifically deals with the rocking mechanism of monolithic shear walls with openings, includes both cases of door and window openings, and considers both cases of kinematic behaviour with one and two centres of rotations. Mathematical expressions for the prediction of the wall segment rotations, the wall segment vertical uplift and the rocking stiffness of the system are derived from the analytical model and presented in the study. The analytical model, which was validated through numerical analyses and the results of an experimental study available in the literature, was used to perform a parametric analysis, in which the lateral rocking behaviour of shear walls with different geometrical and mechanical properties and with different hold down configurations was investigated. Results of the parametric analysis showed that the rocking stiffness of monolithic shear walls with openings is strongly related to their kinematic behaviour. The mathematical expressions found in this study reveal that the kinematic behaviour of these systems mainly depends on the transversal stiffness of lintels and parapets, on the vertical stiffness of the hold downs and on the geometry of the wall segments.